Penerapan PhET Interactive Simulations untuk Meningkatkan Motivasi Belajar Mahasiswa - Zico Fakhrur Rozi; M. Lutfi Firdaus; Endang Suswati (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aims to determine students' responses after implementing biology learning on the pH scale material using the Physics Education Technology (PhET) Simulation. The method used was a survey by distributing questionnaires to 15 Biology Education students at Universitas PGRI Silampari, Lubuklinggau City, South Sumatra Province, who had studied pH scale measurement material using the PhET Simulation. The questionnaire included several indicators: students' interest, benefits, display, and usability of PhET, divided into six statements. The results showed that 86.7% of students strongly agreed that learning using PhET was very interesting, 53.3% of students strongly agreed that PhET motivated and facilitated learning the pH scale, 60% of students strongly agreed that PhET made it easier to understand the pH scale material, and 53.3% of students strongly agreed that the PhET Simulation was easy to understand and its animation design and text met students' needs. In conclusion, the PhET Simulation is very engaging, motivates learning, facilitates material learning, eases material understanding, is easy to use, and its animation design and text align with students' needs. Keywords: PhET, Potential of Hydrogen, Student Response.